Retraction notice to ‘‘Oscillation Properties of Third Order Nonlinear Delay Dynamic Equations on Time Scales’’ [J. Amr. Uni. 3 (2023) 75 – 100] - AL-dheleai, F. S. (Journal of Amran University, 2023)
In this paper, we shall investigate the oscillatory properties of third order nonlinear delay dynamic equations. Applying suitable comparison theorems and by a Riccati transformation technique, we establish some new sufficient conditions which insure that every solution of this equation either oscillates or converges to zero. Our results not only unify the oscillation of third order nonlinear differential and difference equations but also can be applied to different types of time scales with